Evaluating the factors that contribute to the educational success and career choice of Native American students in community college - Wilt, Michelle (My University, 2026)
Community colleges, as open access institutions, play a crucial role in providing educational opportunities for diverse student populations. Native American students represent a unique community college demographic whose cultural backgrounds shape their approaches to higher education. These unique cultural and life experiences can influence retention and degree completion. The theoretical framework for this study was Huffman’s (2001) transculturation theory. The purpose of this research study was to evaluate the factors that contribute to the success of Native American students enrolled within a community college system in the Southwest United States. The purpose of this study was also to provide insight of the Native American community college student experience and their educational and career selection. The study incorporated an explanatory sequential research design, which included a survey and interviews of enrolled Native American community college students. The survey was to learn about the factors that impact the Native American community college experience. The interview focused on how Native American community college students describe the influences of their cultural identity on their career selection and academic journey. This study found that Native American students can be successful in the community college environment, particularly when institutions recognize their unique experiences that influence their educational journey.
Keywords: Community college; Native American students; College experience; Career Selection; Academic major